Cognitive awareness of online-sold prefabricated myofunctional appliances disadvantages among Bandung residents: cross-sectional study - Suryanto, Shenny Shefira; Gayatri, Gita; Suwargiani, Anne Agustina; Zakaria, Myrna Nurlatifah (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACT Introduction: Prefabricated myofunctional appliances (PMAs), commonly known as teeth trainers, are one of myofunctional appliances. These appliances can be used in treating the teeth as well as the muscles. The individuals’ need for dental aesthetics today have led to the trend of marketing PMAs over-the-counter online. This is mostly caused by budget limitations that leads people to seek for alternative and more affordable orthodontic treatments. However, the use of over-the-counter PMAs may pose adverse effects to consumers. This study aims to assess the currents state of knowledge regarding the disadvantages of prefabricated myofunctional appliances among Bandung residents. Methods: This is a descriptive quantitative study, with a cluster random sampling technique. This study involved 100 Bandung residents from 30 different subdistricts, as determined by Slovin formula. The research instrument consisted of questionnaires which included 27-questions with sub variables of dental appearance, PMAs in general, indications, contraindications, advantages, and adverse effects of using over-the-counter PMAs online. The questionnaire was modified based on Bloom's taxonomy. The obtained results were further analyzed using frequent distribution. Results: A total of 30 respondents (30%) were classified as having low knowledge levels. 62 respondents (62%) were categorized as having moderate level of knowledge. and 8 respondents (8%) were categorized as being highly aware of the disadvantages of over-the-counter PMAs. Conclusions: People’s knowledge of the disadvantages of over-the-counter PMAs in Bandung is classified in a moderate level. KEY WORDS: prefabricated myofunctional appliance, myofunctional appliance, orthodontic myofunctional applianceTingkat pengetahuan masyarakat kota Bandung mengenai dampak buruk prefabricated   myofunctional appliances yang dijual secara online: studi cross-sectional ABSTRAK Pendahuluan: Prefabricated myofunctional appliances (PMAs) atau yang dikenal oleh masyarakat awam dengan teeth trainer merupakan sebuah alat myofungsional. PMAs tidak hanya bekerja pada gigi tetapi juga bekerja pada otot. Era modern ini kebutuhan individu akan estetika gigi menyebabkan terciptanya pasar penjualan PMAs secara bebas di online. Hal tersebut disebabkan karena adanya keterbatasan biaya yang menyebabkan individu mencari alternatif perawatan ortodonti yang ekonomis. Penggunaan PMAs yang dibeli bebas secara online dapat menimbulkan bahaya bagi penggunanya. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan masyarakat Kota Bandung mengenai dampak buruk prefabricated myofunctional appliances yang dijual bebas secara online. Metode: Jenis penelitian ini yaitu deskriptif kuantitatif dengan teknik pengambilan sampel cluster random sampling. Penelitian ini dilakukan terhadap 100 masyarakat Kota Bandung dari 30 kecamatan yang telah dihitung menggunakan rumus slovin. Instrumen penelitian yang digunakan adalah kuesioner yang terdiri dari 27 pertanyaan yang mencakup subvariabel penampilan gigi, PMAs secara umum, indikasi, kontraindikasi, kelebihan, dan dampak buruk penggunaan PMAs yang dijual bebas secara online. Kuesioner ini dimodifikasi berdasarkan taksonomi Bloom. Hasil data yang diperoleh selanjutnya dianalisis menggunakan distribusi frekuensi. Hasil: Sebanyak 30 responden (30%) tergolong tingkat pengetahuan rendah, 62 responden (62%) pada kategori sedang, dan 8 responden (8%) memiliki tingkat pengetahuan tinggi terhadap dampak buruk dari PMAs yang dijual secara online. (4) Simpulan: Tingkat pengetahuan masyarakat Kota Bandung mengenai dampak buruk prefabricated myofunctional appliances yang dijual secara online tergolong sedang. KATA KUNCI: prefabricated myofunctional appliance, alat myofunctional, orthodontic myofunctional appliance, online myofunctional appliance.